Assessment of salivary thioredoxin levels in oral lichen planus and oral squamous cell carcinoma - Maryam Amirchaghmaghi; Roya Mahfoozi; Zohreh Dalirsani; Leila Vazifeh Mostaan; Seyed Isaac Hashemy; Mohammad Taghi Shakeri (Wiley, 2021)
Abstract Objective Oral lichen planus (OLP) is a chronic mucocutaneous inflammatory disease, which is considered as a potentially malignant condition and could transformed into oral squamous cell carcinoma (OSCC). Squamous cell carcinmoma is the most common oral cancer. This study aimed to compare salivary thioredoxin levels as an antioxidant protein among patients with OSSC, OLP and healthy subjects. Materials and methods Twenty‐eight patients with OLP, 20 patients with OSCC and 40 healthy people enrolled in this observational study. Saliva samples were collected from all subjects and salivary thioredoxin levels were evaluated by Elisa test. The data were recorded in the check lists and analyzed using SPSS (ver.17). Results Thioredoxin levels of healthy controls were insignificantly higher than OLP and SCC patients (p = 0.135). There was a statistically remarkable indirect relationship between thioredoxin levels and severity of the lesions determined by Thongprasom criteria among OLP patients. The thioredoxin concentration was significantly higher in the keratotic OLP. Among the OSCC patients, the highest levels of thioredoxin were found among patients aged more than 65 years. Salivary thioredoxin levels based on other variables were not significantly different between the studied groups. Conclusion In this study, there was not any significant difference between salivary thioredoxin levels in the OLP and OSCC patients, though it was unremarkable higher in the healthy group compared to the patients; therefore, the role of thioredoxin in the cellular oxidation-reduction status could be suggested; however, further studies are recommended.